Backward-facing step heat transfer of the turbulent regime for functionalized graphene nanoplatelets based water-ethylene glycol nanofluids - Amiri, A.; Arzani, H.K.; Kazi, S.N.; Chew, B.T.; Badarudin, A. (Elsevier, 2016)
Herein, an experimental study on thermo-physical properties of ethylene glycol-functionalized graphene nanoplatelets/water-ethylene glycol nanofluids (EGGNP-WEG) and a numerical study on the convective heat transfer over a backward-facing step are performed. Accordingly, EGGNP was first synthesized covalently to achieve a stable colloidal solution in water-ethylene glycol mixture. Some characterizations were applied to analyze the surface functionality and morphology of EGGNP-flakes. To study the convective heat transfer coefficient in turbulent regime, a numerical study is performed at different weight fractions of EGGNP. According to the results, a higher weight concentration of EGGNP in basefluid indicates a greater extent of convective heat transfer coefficient and thermal conductivity, implying higher heat transfer rate over a backward-facing step.